Socioeconomic inequality and cognitive & physical disabilities among older people in England - Emmanuel Ndenor Sambo (University of East Anglia, Health Economics Group (HEG), 2015)
While the ratio of the younger to older populations grows smaller, the population of the old with health problems is increasingly growing. The likelihood of being disabled is higher for an individual with a lower socioeconomic status than that of an individual with a higher socioeconomic status. The social gradient in health has been found to persist even in the 65 and over age group; therefore, it is important to understand how the associations between disabilities in old age and socioeconomic inequalities thrive. In this study, data from the fifth wave of the English Longitudinal Study of Ageing was used to explore the associations between socioeconomic status and the likelihood of being disabled among non-institutionalised older people in England. Along with marital status, subjective and objective indicators of socioeconomic status were jointly then alternatively used as explanatory variables controlling for age and gender to estimate likelihoods of having cognitive and physical disabilities in old age using Logistic regression models. Results showed that socioeconomic status was associated with the likelihood of being disabled in old age. More than the set of models containing both, the set with either the subjective or objective measures of socioeconomic status explained the relationships between disabilities and socioeconomic status better. Disadvantaged socioeconomic status was associated with higher likelihoods of being disabled whether using the subjective or objective measures of socioeconomic status. From the analysis, education, although attained at younger ages still had significant effects on the likelihood of being disabled. This study contributes to the understanding of the persistent relationship between socioeconomic status and disabilities.
Keywords: 330; Older people; Socioeconomic Inequalities; Cognitive and Physical Disabilities